(3QSGdI aj GdJbdjOs - (3YHGS Hf MSf Hf LYaQ cGTa GdZWGA, J (B1323(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3Gdbhd aj GdJbdjO, hjJe HQSe ChQ GhdgG(B: (3GONd ZjQ hGMO efge gPg GdeSCdI aj GdeHGMK GdCUhdjI agd PGc dCfgG ef eHGMKg ChdG GSJage GdaGVd Gdbejs
(3BNQgG (B:s
(3BNQgG(B: (3dcfg dG hLg dg deG YQaJ ef bUhQ GdGWdGbGJ hYSi Cf jchf ePgH (B.. (3Cf GdJbdjO gh GdYed hYdi aQVg aje jJMbb GdYed GdeGfY ef GdXGgQ HCf GdPj jQJaY eYgs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B8: 58s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs